(untitled) (Polis (Santiago), 2020)
In Mexico, the Natural Protected Areas decree is one of the main government initiatives regarding environmental conservation, assuming it as one of the most effective tools for the conservation of ecosystems, slowing down the expansion of the agricultural frontier and giving identity to selected sites. Recognizing that each conservation area has environmental, economic, social, and historical particularities, the objective of this article is to discuss the tensions that arise between the rank of "common good" subject to National Protected Area regulations and local populations that make use of nature. To do so, we take as a case study the Cofre de Perote National Park, Veracruz, Mexico, ethnographically analyzing the discursive and practical oppositions between those who inhabit and those who designate, plan, organize and take control of the NPAs, and the possibilities of making sustainable use of resources.